MLKL BINDING OR DEGRADING COMPOUND AND PHARMACEUTICAL USE THEREOF - MUN, Hyowon; CHO, Sung Yun; KIM, Pilho; HA, Jae Du; YUN, Chang Soo; HWANG, Jong Yeon; KIM, Hyun Jin; OH, Joon Gyo; LEE, Jisoo; KIM, Hyunjun (2022)
The present disclosure provides a compound of a specific chemical structure binding to MLKL or having an MLKL inhibiting or degrading activity, or pharmaceutically acceptable salts thereof. The present disclosure provides a composition comprising such compound or pharmaceutically acceptable salts thereof. The present disclosure provides the pharmaceutical use of the compound according to the present invention, salts thereof, and a composition comprising same for treating or preventing MLKL-related diseases. The present disclosure also provides a method for treating or preventing MLKL-related diseases, comprising administering to a subject in need of treatment an effective amount of a compound according to the present invention, salts thereof, or a composition comprising same. La présente divulgation concerne un composé d'une structure chimique spécifique se liant à MLKL ou ayant une activité d'inhibition ou de dégradation de MLKL, ou un sel pharmaceutiquement acceptable de celui-ci. La présente divulgation concerne une composition comprenant un tel composé ou ses sels pharmaceutiquement acceptables. La présente divulgation concerne une utilisation pharmaceutique du composé selon la présente divulgation, des sels de celui-ci, et une composition le comprenant pour le traitement ou la prévention de maladies associées à MLKL. La présente divulgation concerne en outre une méthode de traitement ou de prévention de maladies associées à MLKL, comprenant l'administration à un sujet ayant besoin d'un traitement d'une quantité efficace d'un composé selon la présente divulgation, de sels de celui-ci, ou d'une composition le comprenant. 본 개시는 MLKL과 결합하거나, MLKL을 저해 또는 분해하는 활성을 갖는 특정 화학구조의 화합물 또는 이의 약학적으로 허용 가능한 염을 제공한다. 본 개시는 이러한 화합물 또는 이의 약학적으로 허용 가능한 염을 포함하는 조성물을 제공한다. 본 개시는 본 발명에 따른 화합물, 이의 염 및 이들을 포함하는 조성물의 MLKL 관련 질환의 치료 또는 예방용 의약 용도를 제공한다. 본 개시는 또한 본 발명에 따른 화합물, 이의 염 또는 이들을 포함하는 조성물의 유효한 양을 치료가 필요한 개체에게 투여하는 것을 포함하는 MLKL 관련 질환의 치료 또는 예방 방법을 제공한다.